Lower Leg Injury Mechanism Investigation During an IED Blast Under a Vehicle Using an Anatomic Leg Model - Suchoń, Sławomir; Burkacki, Michał; Joszko, Kamil; Gzik-Zroska, Bożena; Wolański, Wojciech; Sławiński, Grzegorz; Tavares, João Manuel R. S.; Gzik, Marek (Frontiers in Bioengineering and Biotechnology, 2021)
Attacks with Improvised Explosive Device (IED) constituted the main threat to, for example, Polish soldiers in Iraq and Afghanistan. Improving safety during transport in an armoured vehicle has become an important issue. The main purpose of the presented research is to investigate the mechanism of lower leg injuries during explosion under an armoured vehicle. Using a numerical anatomic model of the lower leg, the analysis of the leg position was carried out. In all presented positions the stress limit of 160 [MPa] was reached, which indicates bone damage. There is a difference in stress distribution in anatomic elements pointing to different injury mechanisms.